Urban population of the ground beetle Carabus variolosus nodulosus (Coleoptera: Carabidae) in Ljubljana city (Central Slovenia) - Vrezec, Al (Acta entomologica slovenica (Ljubljana), 2021)
A population of the endangered ground beetle Carabus variolosus nodulosus Creutzer, 1799 was discovered in Landscape Park Tivoli, Rožnik and Šišenski hrib in the city center of Ljubljana. In the park area we recorded 12,275 meters of flowing water. In 2012 and 2014, we confirmed the species at 24 out of 48 sampling sites (50%). The estimated minimal number of adult beetles in 2014 ranged from 2295 to 5715. Based on the data collected, we zoned the area with the highest densities. Guidelines for the management of the area are also given in order to maintain or even improve the status of the ground beetle population in Ljubljana. Ljubljana holds the only urban population of the species known so far, which might represent a unique evolutionary significant unit, although its share in the total population in Slovenia is estimated at only 0.02%.
Keywords: Carabidae; Carabus variolosus nodulosus; city park; Coleoptera; conacija; mestni park; mokrotni habitat; Natura 2000; riparian habitat; urban environment; urbano okolje; zonation; Žuželke